Metabolomics strategy for revealing the components in fermented barley extracts with Lactobacillus plantarum dy-1. (January 2021) - Zhao, Yansheng; Wu, Chao; Zhu, Ying; Zhou, Chenguang; Xiong, Zhiyu; Samy Eweys, Aya; Zhou, Hongbin; Dong, Ying; Xiao, Xiang
Graphical abstract: Highlights: 124 components in fermented barley aqueous extract were identified by UPLC-HRMS. PCA distinguished the samples and visualized the process with fermentation time. Metabolomics revealed the change of components in barley with fermentation time. Phytochemicals and metabolites were released and accumulated by L. plantarum dy-1. Indole-3-lactic acid, etc. were identified as significant increasing components. Abstract: Fermentation has been considered as effective tools to promote the functional properties of cereals. In this paper, barley flour was fermented with Lactobacillus plantarum dy-1 ( L. plantarum dy-1) and the main components in the fermented barley aqueous extracts were identified using by ultra-high performance liquid chromatography tandem with high resolution mass spectrometry (UPLC-HRMS), and investigated by metabolomics strategy involved on chemometrics. The barley extracts were prepared at the fermentation time of 0, 4, 8, 12, 16, 20, 24, 28 h, respectively and a total of 124 compounds were detected in the samples. Principal component analysis (PCA) was performed and the results indicated that the fermentation process became to slow down from 16 h until terminated. During fermentation, saccharides, amino acids, nucleosides, and some organic acids decreased, while lipids and bioactive molecules in barley were released and metabolites were accumulated by L. plantarum dy-1. Meanwhile, partial least squares discrimination analysis (PLS-DA) was performed for revealing the characteristic components in fermented barley aqueous extracts, including some functional molecules such as indole-3-lactic acid, phenyllactic acid, homovanillic acid and cafestol, etc., which provided the roles of them and the basis for further investigation on the functional bioactivities and application.